Periodisme i literatura: Aurora Bertrana - Real, Neus (Caplletra. Revista Internacional de Filologia, 2008)
This article relates the activity in the press of the writer Aurora Bertrana with her literature, and it makes evident the interdependence of journalism and literary creation in the first stage of the author’s production. It also analyzes the key role of this interaction in the construction of her image as well as in the consolidation of her intellectual prestige.